Local Management and New Public Management - Irena Bačlija (Central European Public Administration Review)
Economic globalization, growingly differentiated and unstable markets, fiscal crises in light of increasing public expenditure are the elements of an uncertain future for local communities. The latter are captured in the growing demand of users or citizens for quality in public services and in the regulation of the state that (sometimes) limits the creative development and competition on a global market of local communities. In the context of this ever demanding environment functions local administration that has to be reformed in order to conform with the elements of this environment. The article presents the specifics of local management and alongside its reform process by the principles of new public management. Empirical part of the article explains findings of an extensive study of local administrations in the European Union and their reforms with implications that show the effects of reformed local administration on the effectiveness of the entire local community.